PENYAJIAN LAPORAN KEUANGAN BERBASIS AKRUAL PEMERINTAH KABUPATEN KEDIRI - Prihastutik Andayani (Universitas Islam Kadiri, 2019)
Government Accounting Standards is the accounting principles applied in preparing and presenting financial statements presented in the Government Regulation No. 71 Year 2010 accrual. This study aims to determine: (1) Preparedness Kediri Regency Government in implementing the Accrual Based Government Accounting Standards. (2) The preparation of financial statements in accordance Kediri Regency Government Accounting Standards Accrual Based Government. The method used in this study is a qualitative method of secondary data sources: (1) Kediri Regency Government Financial Statements of the fiscal year 2015 consisted of the Budget Realization Report (LRA); Reports Budget Balance Changes Over (Statement of Changes SAL); Balance Sheet; Statements of Operations (LO); Cash Flow Statements (LAK); Statement of Changes in Equity (LPE); Notes to the Financial Statements (CaLK), (2) of Government Regulation No. 71 Year 2010 concerning the Government Accounting Standards. Analysis Techniques used: (1) Data Reduction (data reduction), (2) Data Display (Data Presentation), (3) Conclusion Drawing / verification. From the results of research can be concluded that the District Government kediri already fully apply the standard of preparation of financial statements accrual has been set in Government Regulation No. 71 of 2010 concerning the Government Accounting Standards and Conformity between the Financial Statements of the Government of Kediri with Government Regulation No. 71 of 2010 on Accounting Standards Government